2015
DOI: 10.1590/2177-6709.20.6.082-088.oar
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Clark's twin-block appliance (CTB) and non-extraction fixed mechano-therapy on the pharyngeal dimensions of growing children

Abstract: Introduction: Narrow airway dimensions due to mandibular deficiency can predispose an individual to severe respiratory distress. Hence, treatment with mandibular advancement devices at an early age might help improving the pharyngeal passage and reduce the risk of respiratory difficulties. Therefore, the aim of the current study was to evaluate the mean changes in the pharyngeal dimensions of children with mandibular deficiency treated with Clark's twin-block appliance (CTB) followed by fixed orthodontic treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 29 publications
1
12
0
2
Order By: Relevance
“…This study shows that correction of mandibular retrognathism with a TB appliance in growing patients not only improves the facial profile and intermaxillary relationship but also increases UA dimensions (Ali et al, ; Roque‐Torres, Meneses‐López, Bóscolo, de Almeida, & Neto, ), thus reducing the risk of future respiratory problems (Verma et al, ) and representing a suitable oral appliance to treat children with SAHS (Caridi & Galluccio, ; Zhang et al, ). However, few studies have shown the long‐term effectiveness of TB appliances; therefore, their permanency remains to be determined.…”
Section: Discussionmentioning
confidence: 96%
See 4 more Smart Citations
“…This study shows that correction of mandibular retrognathism with a TB appliance in growing patients not only improves the facial profile and intermaxillary relationship but also increases UA dimensions (Ali et al, ; Roque‐Torres, Meneses‐López, Bóscolo, de Almeida, & Neto, ), thus reducing the risk of future respiratory problems (Verma et al, ) and representing a suitable oral appliance to treat children with SAHS (Caridi & Galluccio, ; Zhang et al, ). However, few studies have shown the long‐term effectiveness of TB appliances; therefore, their permanency remains to be determined.…”
Section: Discussionmentioning
confidence: 96%
“…However, lateral teleradiography of the skull is commonly used in routine clinical practice due to its relative simplicity, accessibility, low cost, and low radiation exposure (Feng et al, ; Rojas, Corvalán, Messen, & Sandoval, ; Santamaria‐Villegas, Manrique‐Hernandez, Alvarez‐Varela, & Restrepo‐Serna, ). Teleradiography remains a valuable diagnostic tool for evaluating the airways (Ali et al, ; Elfeky & Fayed, ; Ghodke et al, ; Jena et al, ; Pavoni et al, ) and can be used to predict OSA (Armalaite & Lopatiene, ). Furthermore, this method has been shown to provide reliable linear measurements and is a valid tool for measuring the dimensions of the nasopharyngeal and retropalatal regions.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations